Implementation Therapy Murottal Al-Quran against Reduction of Anxiety Levels in Patients Pre- Caesarean Section - Maria Suzana; Fitra Mayenti; Riski Nofera Yenita; Fajar Sari Tanberika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Women who are about to undergo childbirth via cesarean section often experience discomfort and anxiety. Excessive anxiety can reduce sleep duration and cause symptoms such as sweating, bloating, and shortness of breath. Based on data from Bengkalis Regional General Hospital (RSUD Bengkalis), there were 1,110 cases of cesarean deliveries recorded in 2023. This study aims to determine the effectiveness of Al-Qur’an murrotal therapy in reducing anxiety levels in pre-cesarean section patients at RSUD Bengkalis. This research uses a quantitative method with a quasi-experimental design. The population in this study consisted of women undergoing cesarean section, with a sample of 16 participants selected using purposive sampling. The instrument used was the HARS (Hamilton Anxiety Rating Scale) questionnaire, and the data were analyzed using univariate and bivariate analysis. The univariate analysis results showed that before receiving Al-Qur’an murrotal therapy, the majority of pre-cesarean section patients experienced moderate anxiety (75%). After the therapy was administered, anxiety levels decreased, with 81.3% of patients falling into the mild anxiety category. The results of the paired sample t-test showed a significant effect of Al-Qur’an murrotal therapy in reducing anxiety levels in pre-cesarean section patients at RSUD Bengkalis, with a p-value of 0.000 (< 0.05).